AUGMENTED REALITY (AR) VERSUS NON-AUGMENTED REALITY (NON-AR) FLASHCARDS ON ENGLISH AS FOREIGN LANGUAGE (EFL)’ WRITING SKILLS: A COMPARATIVE ANALYSIS - Kamila, Lintang Shafa; Tarwiyah, Siti; Annury, Muhammad Nafi (Premise: Journal of English Education and Applied Linguistics, 2026)
Writing is the most challenging EFL skill, requiring linguistic accuracy and creativity. AR and non-AR flashcards offer different pedagogical approaches, yet no systematic comparison exists for EFL writing development. This mixed-methods systematic literature review compares both modalities' effectiveness on writing skills and motivation. Following PRISMA 2020 guidelines, eight studies (2021–2025) with 249 students were analyzed. Non-AR flashcards improved grammar and vocabulary through structured memorization, while AR flashcards enhanced motivation, engagement, and creativity via immersive interaction. Moderator analyses revealed AR flashcards yield greater affective-creative outcomes. Corpus imbalance (5 non-AR vs. 3 AR studies) and Indonesian-context dominance limit generalizability. The study validates Dual-Coding Theory and suggests that integrating both modalities optimizes EFL writing development, warranting further cross-contextual research.